2009
DOI: 10.1159/000259911
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of p53 and Bcl-2 Proteins in Human Papillomavirus-Induced Premalignant Lesions of the Uterine Cervix: Correlation with Progression to Malignancy

Abstract: Objective(s): To analyze aberrant expression of the apoptotic protein p53 and the anti-apoptotic protein Bcl-2 in premalignant lesions of the uterine cervix induced by human papillomavirus (HPV) infection and its significance for early diagnosis of cervical cancer. Materials and Methods: Cytological adequate smears (n = 382) from various grades of squamous intraepithelial lesions (SILs; n = 142), ‘atypical squamous cells of unknown significance’ (ASCUS; n = 128) and normal tissue (n = 112) were investigated im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Studies have shown the over-expression of p53 not only in primary and recurrent CIS cases but also in pre-malignant dysplastic lesions (Bremer et al, 1995;Park et al, 1999;Oh et al, 2004;Singh et al, 2009). In this study, both frequency and intensity of p53 expression was gradually increased along with the severity of lesion and was associated with HPV presence (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Studies have shown the over-expression of p53 not only in primary and recurrent CIS cases but also in pre-malignant dysplastic lesions (Bremer et al, 1995;Park et al, 1999;Oh et al, 2004;Singh et al, 2009). In this study, both frequency and intensity of p53 expression was gradually increased along with the severity of lesion and was associated with HPV presence (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 53%
“…Similarly in NI-HPV types cases (n = 34), most of the cases were from HSIL group (n=10) followed by LSIL (n=13), which suggested that other HPV types are also involved in progression of SILs. According to earlier reports HPV infection is frequently detectable in SIL and CIS cases (Schlecht et al, 2003;Evans et al, 2006) and HPV-16 and 18 are considered as most aggressive HPV subtypes (Singh et al, 2009). Precursor lesions of the uterine cervix those with oncogenic HPV-16 and 18 infections persist longer and progress more quickly than with non-oncogenic infections or without HPV (Schlecht et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guimarães et al, (2005) found by immunohistochemical techniques that expression of Bcl2 in HPV-infected cervical biopsies is not useful for predicting the progression of HPV-related SIL. On the other hand, Singh et al, (2009) noted cytoplasmic expression of Bcl2 protein in cervical dysplasia, a various intensity of immunoreactivity between different cytological grades of cervical smears and an association with the presence of HPV16/HPV18.…”
Section: Apoptotic Markersmentioning
confidence: 93%